Accounting for Oslo Manual: Reflecting on the Past and Setting the Stage for Future Research - Paredes, Alexandre; Damásio, Bruno; Mendonça, Sandro (Foresight and STI Governance, 2025)
The Oslo Manual is the internationally recognized reference for guiding the collection and interpretation of evidence on innovation. This research explores its three-decade-long implementation and influence, emphasizing its role within the research community. We assess the content’s quantity and quality through an advanced bibliometric and textmetric analysis of over 1300 research papers published in internationally indexed journals. Our study offers an evidence-based understanding of the Oslo Manual’s adoption and impact, elucidating disciplinary integration, geographical interest, and reception phases. Notably, the findings unveil the increasing significance of innovation-related topics since its inaugural edition in 1992, with a pronounced surge gaining momentum after 2008. Furthermore, the consistently cited references underscore the researchers’ focus, highlighting the rising importance of innovation and interconnected domains like entrepreneurship, performance, knowledge, and management. This study enhances our understanding of the Oslo Manual’s use and influence, revealing its enduring relevance and its broader impact on shaping innovation research.